Four-Corner Concept: CT-Based Assessment of Fracture Patterns in Distal Radius - Brink, P. R. G.; Rikli, D. A. (Journal of Wrist Surgery, 2016)
Operative treatment using plate fixation is an important adjunct in the treatment of distal radius fractures, although the evidence for its superiority over other modalities remains limited. We propose a new concept for fractures of the distal radius, based on the three-column model of the distal radius, and on the expanding knowledge about the different fracture patterns obtained by evaluation of the distal radius by computed tomographic (CT) scan. All fracture types can be characterized by subdividing the wrist joint into four corners, each with its own characteristics in terms of mobility, stability, and transfer of forces in the intact distal radius. Recognition of the specific fracture types based on this four-corner concept enables a tailored approach to treatment.
Keywords: distal radius fractures; intra-articular fractures